Transforming growth factor beta‐induced p.(L558P) variant is associated with autosomal dominant lattice corneal dystrophy type IV in a large cohort of Spanish patients. (22nd May 2019) - Campos‐Mollo, Ezequiel; Varela‐Conde, Yago; Arriola‐Villalobos, Pedro; Cabrera‐Beyrouti, Rubén; Benítez‐del‐Castillo, José‐Manuel; Maldonado, Miguel J.; Escribano, Julio
Abstract: Importance: Rare transforming growth factor beta‐induced ( TGFBI ) gene variants are involved in autosomal dominant corneal dystrophies (CDs) with heterogeneous clinical features. Background: The purpose of this study was to analyse TGFBI gene variants and genotype‐phenotype correlations in a cohort affected by atypical stromal CD. Design: Retrospective cohort study (from May 2014 to September 2017). Participants: Thirty‐five individuals from 10 unrelated South European families presenting atypical lattice CD (LCD) were included. Methods: Corneal phenotypes were assessed by slit‐lamp examination and optical coherence tomography (OCT). Contrast sensitivity was measured under mesopic conditions. Genomic DNA was obtained from blood samples, and all 17 TGFBI exons were screened for variants by Sanger sequencing. Main Outcome Measures: p.(L558P) variant of TGFBI gene. Results: The p.(L558P) variant was identified in 22 members of the 10 families diagnosed with atypical LCD, characterized by late‐onset and absence of recurrent erosion syndrome. OCT revealed punctiform deposits in the deep‐mid stroma and normal anterior stroma. This variant was demonstrated to be transmitted with the disease according to autosomal dominant inheritance in most families. Conclusions and Relevance: To the best of our knowledge, we describe a detailed clinical characterization of the largest CD cohort carrying the TGFBI p.(L558P) variant. We propose that the atypical phenotype of this recently reported alteration can be classified as a form of LCD type IV. The results show that OCT and anterior‐posterior analysis of the stromal location of the opacities, along with a genetic analysis of TGFBI, are required to ensure accurate diagnosis and management of CDs.